Influence of folic acid knowledge on effective folic acid intake in Chinese pregnant women: a cross-sectional study - You Jing Jin; Hae Won Kim (Korean Society of Women Health Nursing, 2023)
Purpose This study aimed to investigate the current status of effective folic acid intake and the level of folic acid knowledge of Chinese pregnant women and to analyze the relationship between effective folic acid intake and folic acid knowledge. Methods From November 2021 to May 2022, 140 pregnant women at Yantai Yuhuangding Hospital in the Chinese province of Shandong, answered questions about their general characteristics, folic acid intake, and folic acid knowledge. The data were analyzed using the t-test, chi-square test, and logistic regression analysis, and were presented with frequency with percentage or mean±standard deviation. Results Only 16.4% of the pregnant women (n=23) took folic acid effectively, using the following four criteria. Of all pregnant women who took folic acid, 72.2% took folic acid starting 1 month before pregnancy, 70.8% took folic acid up to 3 months after pregnancy, 36.8% took 400 μg every time, and 78.6% took folic acid more than 24 days every month. The score for folic acid knowledge was relatively high (5.61±2.18 on a scale of 0-9). A higher folic acid knowledge score correlated with more effective folic acid intake (t=4.10, p<.001). Conclusion Our study shows that the current recommendations to prevent neural tube defects through effective folic acid intake supplementation are not being fully implemented in China. Furthermore, folic acid knowledge was positively correlated with the effectiveness of its intake. Future education related to effective folic acid intake should emphasize the four methods of effective folic acid intake, especially regarding the recommended dose of 400 μg every time.